Harmful Algal Bloom Species Associated With Massive Atlantic Salmon Mortalities While Transported Through The Gulf Of Penas, Southern Chile. - Toro, Carolina; Alarcón, César; Pacheco, Hernán; Salgado, Pablo; Frangópulos Rivera, Máximo Jorge; Rodríguez, Francisco; Fuenzalida, Gonzalo; Raimapo, Roberto; Pizarro, Gemita; Guzman, Leonardo (My University, 2020)
"During January (Austral Summer) 2017, in the Gulf of Penas (47° S), a mortality of around 130 tons of farmed smolts of Atlantic salmon occurred while they were transported by three wellboats from the Aysén region (45° S) to the western area of the Strait of Magellan (54° S). The ichthyotoxic Karenia cf. mikimotoi was identified as the likely causative agent of mortality. Therefore, four field researches were conducted between February 2017 and March 2018 to assess the abundance and distribution of Karenia in the Gulf and surrounding areas. In addition, data from this period provided by the Red Tide Monitoring Programme were considered. The results showed the presence of different species of Karenia (K. cf. mikimotoi, K. cf. brevis, K. cf. bicuneiformis). The highest abundances occurred in the Gulf of Penas (700 and 4,500 cells L-1 , in February 2017 and 2018, respectively). The distribution of these species ranged from Paso Tamar (52°S), Magellan region (100 cells L-1) to Inchemo island (45° S), Aysén region (200 cells L-1), both in March 2017. Interestingly, Azadinium spp. for the first time were also identified at the Magellan region during 2017, between Puerto Eden (49° S) and Mariotti Islets (55° S), reaching up to 2,800 cells L-1 at Estero Wickham (53°S) in February 2018. The abundances and distributions of Karenia spp. and Azadinium spp suggest that their densities increased initially in the open Pacific Ocean, followed by a passive hydrodynamical transport to the Gulf of Penas, and later on to the Magellan region fjords."
Keywords: Gulf Of Penas; Aysén-Magellan Regions; Fjords; Red Tide-Monitoring Programme; Ichthyotoxins; Karenia Spp; Azadinium Spp